1950
DOI: 10.1084/jem.92.2.121
|View full text |Cite
|
Sign up to set email alerts
|

The Renal Mechanism for Urate Excretion in the Dalmatian Coach-Hound

Abstract: Three findings characterize the unusual purine metabolism of the Dalmatian dog (1): (a) Unlike other dogs, the urine of the pure bred Dalmatian contains large amounts of urate and relatively small amounts of allantoin, (b) per unit body weight, the urinary urate excretion of the Dalmatian is several times that of man, (c) although the Dalmatian excretes more urate than man per unit weight, this is accomplished at a plasma urate level much lower than that of man. In other words, the renal clearance of urate per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1953
1953
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 3 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Sperling et al 38 suggest that the solubility of uric acid is maintained by THP and that increased uric acid content may result in decreased quantities of THP or reduced activity of THP. Recall that results of some studies 8,[27][28][29][30][31] of purine metabolism in Dalmatians were interpreted to indicate that the magnitude of increased serum and urine uric acid concentrations was similar in males and females. If those observations are valid, they indicate that increased urine uric acid concentration would likely decrease urine THP concentration in male and female Dalmatians and therefore would be unlikely to explain the sex-related difference in detection of urate uroliths.…”
Section: Small Animals/ Exoticmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperling et al 38 suggest that the solubility of uric acid is maintained by THP and that increased uric acid content may result in decreased quantities of THP or reduced activity of THP. Recall that results of some studies 8,[27][28][29][30][31] of purine metabolism in Dalmatians were interpreted to indicate that the magnitude of increased serum and urine uric acid concentrations was similar in males and females. If those observations are valid, they indicate that increased urine uric acid concentration would likely decrease urine THP concentration in male and female Dalmatians and therefore would be unlikely to explain the sex-related difference in detection of urate uroliths.…”
Section: Small Animals/ Exoticmentioning
confidence: 99%
“…[5][6][7] In addition to reduced hepatic conversion of uric acid to allantoin, a membrane transport defect has been identified in the kidneys of Dalmatians that reduces renal tubular reabsorption of uric acid. [8][9][10] Dalmatians also remove some uric acid from the general circulation by renal tubular secretion. [11][12][13][14] Whereas the daily urinary excretion of uric acid by non-Dalmatian breeds is approximately 15 to 50 mg, the daily urinary excretion of uric acid by Dalmatians is 200 to 800 mg. 15 Hyperuricuria predisposes Dalmatians to urate urolithiasis.…”
mentioning
confidence: 99%
“…In amphibians, the rise in renal am monia excretion during acidosis occurs un der conditions of no change in either urine pH or urine flow thereby indicating that the metabolic production of ammonia by the kidney must be increased [79], Studies of X. laevis and R. temporaria kidneys have shown that, among the amino acids, gluta mine and alanine show the greatest rate of in vitro renal deamination [3], and in Xenopus, Stetson [72] has found that acidosis provokes a 30% rise in the activity of renal glutami nase. These data suggest that at least in Xenopus, glutamine is an important am monia source for the response of ammonia excretion in acidosis and that the regulation of renal ammonia production in this species involves metabolic adaptations characteris tic of mammalian species.…”
Section: Ammoniamentioning
confidence: 99%
“…This occurs as a result not only of a relatively low uricase activity, but, more importantly, also ofa net renal secretion of urate. Wolfson et al [79] found the renal clearance of urate by dalma tian hounds to be 2.3 times the glomerular filtration rate (measured by exogenous creatinineclearance). The kidneysof rabbitand guinea pig also display net secretion of urate.…”
Section: Uric Acidmentioning
confidence: 99%
“…Although secretion was easily delineated in the Dalmatian coach hound (4)(5)(6), special experimental conditions were necessary for its substantiation in other species. Uric acid clearance in excess of simultaneous creatinine clearance, indicative of tubular secretion of urate, was noted by Poulsen and Praetorius in rabbits made hyperuricemic by the intravenous infusion of urate (1).…”
mentioning
confidence: 99%